A study of user preferences when choosing applications for smartphones used to order food from supermarkets - Shvetsova Svetlana (E3S Web of Conferences, 2023)
This article explores user preferences when choosing applications. The analysis was carried out on the example of applications used to order food delivery from supermarkets. We reviewed and compared a group of factors on which user preferences are based. The analysis of user proposals was carried out in regions where the cold arctic climate prevails most of the year. The climatic feature of the regions where users live is one of the determining factors in the choice of applications installed in a smartphone and used to order food. The analysis carried out showed quantitative indicators of user preferences in the choice of applications. The analysis data can be relevant for services marketing services involved in the development and optimization of applications for ordering food.